Pengaruh Tingkat Pendidikan, Disiplin Kerja, Dan Kepemimpinan Terhadap Kinerja Pegawai Kantor Desa Jaya Bakti - Rohani Fitriyani; Ery Teguh Prasetyo; Dody Kurniawan (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2024)
This research aims to examine the influence of education level, work discipline and leadership on Jaya Bakti Village employees. The population in this research is Jaya Bakti village employees. The sampling technique used in this research was a total of 50 employee data samples. The analysis method uses multiple linear regression methods. The test results proved that the variables Educational Level (X1), Work Discipline (X2), Leadership (X3), and Employee Performance had a significant simultaneous effect with the results of multiple linear analysis and the F test. The calculation results were obtained from F-count > from F- table (173.138 > 2.80), while the significant partial effect via the t test was obtained from the t-calculated value on the Education Level variable (X1) of 4.970, the t-calculated value on the Work Discipline variable (X2) was 6.243 t-calculated value The Leadership variable is 2.677 and is greater than the t-table of 2.012. The research results show that the level of education, work discipline and leadership simultaneously have a positive and significant effect on the performance of Jaya Bakti village employees.